A next-generation Fab library platform directly yielding drug-like antibodies with high affinity, diversity, and developability - Fortunato Ferrara; Adeline Fanni; Andre A. R. Teixeira; Esteban Molina; Camila Leal-Lopes; Ashley DeAguero; Sara D’Angelo; M. Frank Erasmus; Laura Spector; Luis Antonio Rodriguez Carnero; Jianquan Li; Thomas J. Pohl; et al. (mAbs)
We previously described an in vitro single-chain fragment (scFv) library platform originally designed to generate antibodies with excellent developability properties. The platform design was based on the use of clinical antibodies as scaffolds into which replicated natural complementarity-determining regions purged of sequence liabilities were inserted, and the use of phage and yeast display to carry out antibody selection. In addition to being developable, antibodies generated using our platform were extremely diverse, with most campaigns yielding sub-nanomolar binders. Here, we describe a platform advancement that incorporates Fab phage display followed by single-chain antibody-binding fragment Fab (scFab) yeast display. The scFab single-gene format provides balanced expression of light and heavy chains, with enhanced conversion to IgG, thereby combining the advantages of scFvs and Fabs. A meticulously engineered, quality-controlled Fab phage library was created using design principles similar to those used to create the scFv library. A diverse panel of binding scFabs, with high conversion efficiency to IgG, was isolated against two targets. This study highlights the compatibility of phage and yeast display with a Fab semi-synthetic library design, offering an efficient approach to generate drug-like antibodies directly, facilitating their conversion to potential therapeutic candidates.